Education and Aging: A Comparative Analysis between UNATI/UEM and the Brazilian Charter for Smart Cities - Ferreira de Alvarenga, João Vitor (2024)
This article aims to conduct a comparative analysis between the University of the Third Age (UNATI/UEM) and the Brazilian Charter for Smart Cities. To achieve this objective, we conducted qualitative research of a documentary nature, iden-tifying convergent aspects between the two documents. The results reveal six key points of convergence: the emphasis on quality of life for the elderly, the planning of social actions to support this demographic, access to cultural and educational services, encouragement of technological advancements, the training of professionals to care for the elderly through teaching, research, and outreach, and healthcare provisions for the elderly. The study concludes that developing aging policies and training human resources for elderly care can reshape perceptions of aging, ultimately enhancing the quality of life for the elderly.